2017
DOI: 10.1038/s41598-017-17081-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep mutational scanning of S. pyogenes Cas9 reveals important functional domains

Abstract: RNA-guided endonucleases (RGENs) have invigorated the field of site-specific nucleases. The success of Streptococcus pyogenes Cas9 (SpCas9) has led to the discovery of several other CRISPR-associated RGENs. As more RGENs become available, it will be necessary to refine their activity before they can be translated into the clinic. With this in mind, we sought to demonstrate how deep mutational scanning (DMS) could provide details about important functional regions in SpCas9 and speed engineering efforts. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…In fact, SpyMac demonstrated negligible editing on the tested 5 0 -AAAA-3 0 target sequence within the PVALB gene. To address sites with low modification efficiencies, we introduced two mutations (R221K and N394K) into SpyMac that had been previously identified by deep mutational scans of SpyCas9 to increase editing efficiency 34 . We refer to this variant as an increased editing SpyMac (iSpyMac) due to its elevated modification efficiencies on all tested 5 0 -NAAN-3 0 targets, even editing on sites that SpyMac is unable to access, such as 5 0 -AAAA-3 0 PAM sites (Fig.…”
Section: Discovery Of Smaccas9mentioning
confidence: 99%
“…In fact, SpyMac demonstrated negligible editing on the tested 5 0 -AAAA-3 0 target sequence within the PVALB gene. To address sites with low modification efficiencies, we introduced two mutations (R221K and N394K) into SpyMac that had been previously identified by deep mutational scans of SpyCas9 to increase editing efficiency 34 . We refer to this variant as an increased editing SpyMac (iSpyMac) due to its elevated modification efficiencies on all tested 5 0 -NAAN-3 0 targets, even editing on sites that SpyMac is unable to access, such as 5 0 -AAAA-3 0 PAM sites (Fig.…”
Section: Discovery Of Smaccas9mentioning
confidence: 99%
“…It is likely that the PAM preference identified for iSpyMacCas9 in rice would largely hold true for other plant species, although this requires future exploration. In our study, we found that iSpyMacCas9 was indeed more potent than SpyMacCas9, revealing the importance of the R221K and N394K mutations for improved activity ( Spencer and Zhang, 2017 ). It is conceivable that protein engineering may be further used to relax iSpyMacCas9 PAM requirements as well as enhance its nuclease activity.…”
Section: Discussionmentioning
confidence: 61%
“…We synthesized a rice codon-optimized PI domain from SmacCas9 and replaced the corresponding PI domain in two versions of SpyCas9, pcoCas9 ( Li et al., 2013 ), and zCas9 ( Xing et al., 2014 ), which generated pco-SpyMacCas9 and z-SpyMacCas9. R221K and N394K mutations, previously identified through deep mutational scans, can increase SpyCas9 nuclease activity ( Spencer and Zhang, 2017 ). We further introduced these two mutations to create pco-iSpyMacCas9 and z-iSpyMacCas9.…”
Section: Resultsmentioning
confidence: 99%
“…Other concerns about CRISPR-Cas9 technology are related to the Cas9 protein itself as it was shown to induce an immune response when delivered by adeno-associated virus in mice, making immunogenic side effects a concern (Chew et al, 2016). There are also concerns about the specificity of Cas9 and the limited number of sites which can be targeted due to the requirement of the PAM (Spencer and Zhang, 2017). Protein engineering efforts led to the identification of mutations in Cas9 that alter its PAM recognition and enhance its fidelity and recognize other motifs (Kleinstiver et al, 2015;Kleinstiver et al, 2016;Leenay and Beisel, 2017).…”
Section: Biosafety Concerns About Genome-edited Plantsmentioning
confidence: 99%